Analisis SWOT Potensi Zakat Produktif di Indonesia: Studi Pendekatan NVivo dan Literature Review - Doni Yusuf Bagaskara; Rohmadi Rohmadi (PUTRA JAWA PUBLISHER, 2025)
The main objective of this study is to conduct a SWOT analysis on the potential of Productive Zakat in Indonesia using the NVivo method. The research methodology involves qualitative analysis along with the NVivo approach and a review of existing literature. The data analysis methods consist of: (1) categorizing news articles based on SWOT analysis using NVivo 14 software; (2) creating visual representations through hierarchical diagrams and examining the relationship between media articles using SWOT analysis; (3) generating word clouds to identify commonly discussed topics in media articles; and (4) assessing the significance of correlations among media articles related to